2018
DOI: 10.1002/jcla.22664
|View full text |Cite
|
Sign up to set email alerts
|

Can lactate levels be used as a marker of patent ductus arteriosus in preterm babies?

Abstract: High lactate levels are multifactorial and usually indicate impairment of tissue perfusion. There are a number of factors that can lead to impaired tissue perfusion in preterm infants. For the first time in this study, it was shown that lactate levels did not significantly increase in the presence of hemodynamically significant PDA. This may be due to the fact that peripheral tissue perfusion in the presence of hemodynamic PDA does not deteriorate enough to cause an increase in anaerobic metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(27 reference statements)
4
2
0
Order By: Relevance
“…This data comes in agreement with the studies of Okur et al and Visconti et al [26,30] which revealed that hsPDA patients have higher mortality rate compared with non-hsPDA patient. On the other hand, Okur et al [26] reported no significant difference between hsPDA group and non-hsPDA groups regarding mortality.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This data comes in agreement with the studies of Okur et al and Visconti et al [26,30] which revealed that hsPDA patients have higher mortality rate compared with non-hsPDA patient. On the other hand, Okur et al [26] reported no significant difference between hsPDA group and non-hsPDA groups regarding mortality.…”
Section: Discussionsupporting
confidence: 93%
“…Pulmonary hemorrhage was significantly associated with HS PDA when compared to non-hsPDA (P = 0.031). This data came in agreement with Okur et al [26] who reported no difference in early neonatal sepsis, IVH, BPD between hsPDA and non-hsPDA groups. However, Lee et al [27] found more infants suffering from early sepsis in the PDA group when compared with the non-PDA group.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations